The complete mitochondrial genome of Hemiclepsis yangtzenensis (Clitellata: Glossiphoniidae). Issue 5 (4th May 2022) - Yi, Ti-Lin; Pei, Meng-Ting; Xu, Zhi-Wei; Yang, Dai-Qing
Abstract: We present the complete mitochondrial genome sequence of a recently described new leech species named Hemiclepsis yangtzenensis Yang & Bolotov 2021 collected in central China. The mitochondrial genome is 14, 984 bp in length and consists of 13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes, all of which are encoded on a single strand. It exhibited a strong A + T bias of 72.87%. There is a large non-coding region (614 bp) located between the tRNA-Arg and tRNA-His genes, wherein we identified 40 short dispersed repeats, 13–22 bp long, 8 of which were direct, 20 inverted, and 12 palindromic. Phylogenetic analysis of 20 Hirudinea mitogenome sequences resolved monophyletic Glossiphoniidae, and H. yangtzenensis formed a sister lineage with Glossiphonia concolor.